Penerapan Augmented Reality pada Pengenalan Hewan Purbakala berdasarkan Jenis Makanan berbasis Android - Shabrina Ziha Fidela; Rr. Hajar Puji Sejati (Universitas Hamzanwadi, 2023)
Ancient animals are animals that lived in the past and are now extinct. After the extinction of ancient animals, various information about these animals can only be seen through books and museums, where they show only fossils of ancient animals. Most people know the ancient animals as T-Rex, but in fact they have a variety of species up to their food type. The purpose of this research is to create an application to introduce ancient animals that have been divided by food type, namely carnivores, herbivores, and omnivores by utilizing augmented reality to replace books and museums. This research used quantitative research in the form of questionnaires to 7D class SMP Negeri 3 Mlati. The questionnaire was processed using the likert scale and the Interval Level Value (NJI) to obtain the application eligibility interval scale. The method used to build applications using the Multimedia Development Life Cycle consists of six stages: concept, design, collecting material, assembly, testing, and distribution. The test on this research used black box, angle and distance testing, and questionnaire results. The result of this research showed that functionally the features and benefits of the application in introducing ancient animals using augmented reality to people earned a merit of 4.19. Based on the NJI interval scale, the value of 4.19 is a good category so that applications are worth distributed to the public in place of books and museums.